2023
DOI: 10.1002/chem.202302374
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Photochromic Phosphines by Pd‐Catalyzed Annulation Reaction of Alkynes Bearing Phosphinyl Substituent with a Silacyclopropene

Akshitha Selvaraj,
Marie Cordier,
Marc Devillard
et al.

Abstract: The synthesis of phosphines with light controlled basicity is presented in this study. A methodological approach for the preparation of these unconventional photochromic phosphines based on a dithienylethene organic moiety is reported. It relies on the palladium‐catalyzed annulation of alkynyl phosphines in the presence of a 2,3‐Dithienylsilacyclopropene. Accordingly, a diphenyphosphino moiety is connected to the organic photochrome thanks to different linkers. Their influence on the photochromism and on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In our previous paper, 13 we have shown that the parent Nprotected dibenzo [1,2,6]triazonines are available via a reaction sequence that involves formation of the diazo unit as the final step. This step can be carried out either by reductive cyclization of bis(o-nitrobenzyl)amines or by oxidative cyclization of bis(o-aminobenzyl)amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous paper, 13 we have shown that the parent Nprotected dibenzo [1,2,6]triazonines are available via a reaction sequence that involves formation of the diazo unit as the final step. This step can be carried out either by reductive cyclization of bis(o-nitrobenzyl)amines or by oxidative cyclization of bis(o-aminobenzyl)amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This last method provided (E)-3,8-diiodo-12-tosyl-12,13-dihydro-11H-dibenzo[c,h]-Scheme 1. Synthesis of (E)-3, h][1,2,6]triazonine (E)-4a [1,2,6]triazonine 4a in 35% yield, while reductive conditions led to 4a as a complex mixture with dehalogenated products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations